2018
DOI: 10.1186/s12931-018-0843-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmented expression of Ki-67 is correlated with clinicopathological characteristics and prognosis for lung cancer patients: an up-dated systematic review and meta-analysis with 108 studies and 14,732 patients

Abstract: BackgroundLung cancer ranks as the leading cause of cancer-related deaths worldwide and we performed this meta-analysis to investigate eligible studies and determine the prognostic effect of Ki-67.MethodsIn total, 108 studies in 95 articles with 14,732 patients were found to be eligible, of which 96 studies reported on overall survival (OS) and 19 studies reported on disease-free survival (DFS) with relation to Ki-67 expression in lung cancer patients.ResultsThe pooled hazard ratio (HR) indicated that a high K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 130 publications
5
60
0
Order By: Relevance
“…How to grade Ki67 expression remains therefore an open question. A 20% cutoff has been reported (38). Nonetheless, a previous meta-analysis assessing various cut-off levels of Ki67 in regards to prognosis suggested a visual cut-off >25% to provide a higher discriminatory power in mortality risk compared with the remaining cut-off points evaluated (39).…”
Section: Cutoff Of 25% For Ki67 Expression Is a Good Classification Tmentioning
confidence: 98%
See 1 more Smart Citation
“…How to grade Ki67 expression remains therefore an open question. A 20% cutoff has been reported (38). Nonetheless, a previous meta-analysis assessing various cut-off levels of Ki67 in regards to prognosis suggested a visual cut-off >25% to provide a higher discriminatory power in mortality risk compared with the remaining cut-off points evaluated (39).…”
Section: Cutoff Of 25% For Ki67 Expression Is a Good Classification Tmentioning
confidence: 98%
“…Indeed, head-to-head comparisons between scores from automated and pathologist-based techniques in terms of prognostic value have been rarely reported, and discrepant findings in breast cancer have been obtained (35)(36)(37). Previous reports (38,39) discussed the role of Ki67 expression in lung and breast cancers, examining ways to define the cutoff of Ki67 expression. Similar questions remain for CRC.…”
Section: Cutoff Of 25% For Ki67 Expression Is a Good Classification Tmentioning
confidence: 99%
“…A large number of studies have reported the clinical and prognostic value of Ki-67/MKI67 in various malignancies, such as breast cancer 9, cervical cancer 10, glioma 11, colorectal cancer 12 and hepatocellular carcinoma 13. Our research group previously conducted systematic meta-analyses to explore the prognostic role of Ki-67/MKI67 in lung cancer 14, hepatocellular carcinoma 13, cervical cancer 15, glioma 16 and colorectal cancer 17 and found that Ki-67/MIB-1 could be an independent prognostic biomarker in these types of carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The Ki‐67 labelling index has been examined in several types of malignant tumours. Previous studies reported the random counting of cells in representative areas and in hot‐spots (where several tumour cells express Ki‐67) 5,16,23 . Regarding LADC, tumour cells were predominantly counted in representative areas and successfully demonstrated the prognostic benefits of the Ki‐67 labelling index 5,17,23 .…”
Section: Discussionmentioning
confidence: 95%
“…The proliferative activity of neoplastic cells, measured by the Ki‐67 labelling index, is one of the most useful diagnostic and prognostic markers in patients with malignant tumours 1–5 . Previous studies have confirmed its benefit and proposed cut‐off values to differentially diagnose malignant from benign tumours and assess their outcomes 6–12 …”
Section: Introductionmentioning
confidence: 99%